Aprendizagem docente das egressas dos cursos de Pedagogia: docência com a infância - Fleig, Maria Talita (2017)
This doctorate research is in the Formation, Knowledge and Professional Development research line of the Post-graduation Program on Education of the Federal University of Santa Maria (UFSM), Rio Grande do Sul, Brazil. This study is referenced on the qualitative research principles, being characterized as a social-historical cultural narrative approach. It aims to approximate the subjectivity of the participants to the objectivity of the cultural and institutional backgrounds, historically dated. By semi structured interviews, organized by guide topics and carried on seven former students of UFSM Pedagogy Course, diurnal and nocturnal period, it seeks for understanding the learning of being teacher, regarding the childhood teaching practice by the formative processes experienced. The studies of Bakhtin (1988, 2011), Bolzan (2002, 2007, 2014, 2016), Davidov & Márkova (1987), Freitas (1998, 2002, 2007), Huberman (1992), Imbernón (2010, 2011), Isaia & Bolzan (2008, 2010, 2011); Leontiev (1978, 1984), Marcelo (1999, 2009), Sarmento (2005, 2009), Tardif (2014), and Vygostki (1991, 1995, 1996, 2001, 2011) were the references used in the theoretical and methodological approach, contributing to the comprehension of the tessitura on the teaching learning, from the narratives of former students, teachers who act or have acted on child education or on the early basic education. The finding on this research signals the teaching learning as a central category, which interlace the categorical dimensions: formative trajectory, teaching study activity, childhood teaching and organization of the pedagogical work for childhood. When these dimensions are focused, they evince the category elements, grouped by the internal relations they establish by the recurrence of the excerpt from the former student‟s narratives. In this tessitura, the formative processes were constituted as a transversal element, since it follows and passes by all the process of constituting on the profession. The university cultures and the school cultures configure itself/themselves as contextual elements, considering they comprise the initial formation and also evince the return to the formative institution with the possibility of dialogue and maintenance of the bond of study and investigation, completing and problematizing the teaching actions on primary education. We evince that the negotiation, the transgression and the articulation among teachers are possible, enabling the school environment permeable to changes, with processes of collective reflection, showing the authorship and the professorial creation. Shared protagonism, which evolves the relations with children, coworkers and families in the contexts of classroom and institutional management is a goal to the former student‟s, who recognize that when the initiative and mobilization appear from a teacher or a small group, they can take longer to be accepted and consolidated in the institution, but they fortify and instigate a change trigger. The school context created and activated teaching actions, evoking to discussion the knowledge manifested about cultural appropriation of writing in childhood, considering that this is a sociocultural construction. The propose of this research, which defines the thematic field, is related to the needs and the possibilities of studies that support the relations and investigative practices on primary and college education, where the problematization of childhood teaching becomes basic in the construction and [re]signification of teaching knowledge, with the professional insertion of former students, configuring the learning of being teacher.